ANALISIS YURIDIS KEKUATAN HUKUM ATAS SERTIPIKAT SATUAN RUMAH SUSUN HUNIAN ATAU CAMPURAN PASCA TERBITNYA UNDANG-UNDANG NOMOR 20 TAHUN 2011 (STUDI DI KOTA MEDAN) - M. RIDWAN (PREMISE LAW JURNAL, 2017)
ABSTRACT Higt rise is not of the alternatives for problem solving the need for huising and settlemet, especially in urban area which population grows rapidly ; bilding high rise is a must since there the is limited in land area and the increasing demand for boards. The research problems were as follows ; how about the regulation which regulated the status of the ownership of land right certificate of residential or mixture higt rise units in law No 20/2011 on High Rise, how about the problems in residential high rise and renewel, and how about the responsibility of its ownership in strata titly system in maintaining land and building right and the higt rice facility. Keywords : Certificate, High Rise Unit, Residence, Mixture